2021
DOI: 10.1080/21655979.2021.2008659
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circFLNA inhibits the development of bladder carcinoma through microRNA miR-216a-3p/BTG2 axis

Abstract: Recent studies have shown that circular RNA circFLNA is abnormally expressed in a variety of malignant tumors, but its role and mechanism in bladder carcinoma (BCa) are still unclear. The present paper aims to contribute to research on the effects and mechanism of circFLNA on the malignant phenotype of BCa. In this study, the expressions of circFLNA, miR-216a-3p and BTG2 in BCa and BCa cells (EJ, T24, 5637, TCC-SUP) were detected by qRT-PCR. EdU staining, colony formation, Transwell assay, wound healing assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Circular RNA (circRNA) contain abundant miRNA binding sites and can act as miRNA sponges to regulate the posttranscriptional levels of their target genes (65) (Figure 2B). Lin et al (66) demonstrated that the expression of circRNA, which is circularized from exons 9-15 of the filament protein A (FLNA) gene (circFLNA), is downregulated in BC. The overexpression of circFLNA resulted in the significant downregulation of SOX2 expression.…”
Section: Regulation By Circular Rnamentioning
confidence: 99%
See 2 more Smart Citations
“…Circular RNA (circRNA) contain abundant miRNA binding sites and can act as miRNA sponges to regulate the posttranscriptional levels of their target genes (65) (Figure 2B). Lin et al (66) demonstrated that the expression of circRNA, which is circularized from exons 9-15 of the filament protein A (FLNA) gene (circFLNA), is downregulated in BC. The overexpression of circFLNA resulted in the significant downregulation of SOX2 expression.…”
Section: Regulation By Circular Rnamentioning
confidence: 99%
“…Lin et al. ( 66 ) demonstrated that the expression of circRNA, which is circularized from exons 9–15 of the filament protein A ( FLNA ) gene (circFLNA), is downregulated in BC. The overexpression of circFLNA resulted in the significant downregulation of SOX2 expression.…”
Section: Regulation Of Sox2 Expression In Bladder ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary antibody (1:2000, SolelyBio, Beijing, China) was subsequently added to be incubated for 90 min. Finally, the ECL reagent was added to expose the bands, which were further quantified with the Image J software [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…BTG2 negatively mediates CCND1 and reduces the expression level of FoxM1 via suppressing the association of CCNB1/CDKs [ 147 ]. CircFLNA reduced the bladder tumor growth via miR-216a-3p/BTG2 axis [ 148 ].…”
Section: Autophagy Apoptosis and Cell Cycle Regulationmentioning
confidence: 99%